2015
DOI: 10.1039/c5cc01003a
|View full text |Cite
|
Sign up to set email alerts
|

DNA-templated in situ growth of AgNPs on SWNTs: a new approach for highly sensitive SERS assay of microRNA

Abstract: In this communication, we find that the single-walled carbon nanotubes (SWNTs) can demonstrate an excellent ssDNA concentration-dependent surface enhanced Raman scattering (SERS) effect after the decoration of DNA-templated in situ grown AgNPs on the surface. Inspired by this, the SWNT@AgNPs hybrid nanocomposite was employed to achieve microRNA detection which is also sensitive to crude extraction from human breast cancer cells and even patient tissues before and after chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…As a typical layered carbon-based 1D nanomaterial, carbon nanotubes exhibit stable and excellent optical properties, as well as distinctive Raman scattering features that are induced from the chemical enhancement. In a previous study, Zheng et al [79] found that single-walled carbon nanotubes (SWNTs) can be bundled with ssDNA molecules to form a SERS-active SWNTs/DNA/Ag complex after reducing silver ions to silver nanoparticles on the surface (Figure 3C). The SERS signal intensity, jointly attributed to chemical and plasmonic enhancement, showed a positive correlation with the number of ssDNA aptamers for miR-21; the limit of detection (LOD) was 10 pM.…”
Section: D Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…As a typical layered carbon-based 1D nanomaterial, carbon nanotubes exhibit stable and excellent optical properties, as well as distinctive Raman scattering features that are induced from the chemical enhancement. In a previous study, Zheng et al [79] found that single-walled carbon nanotubes (SWNTs) can be bundled with ssDNA molecules to form a SERS-active SWNTs/DNA/Ag complex after reducing silver ions to silver nanoparticles on the surface (Figure 3C). The SERS signal intensity, jointly attributed to chemical and plasmonic enhancement, showed a positive correlation with the number of ssDNA aptamers for miR-21; the limit of detection (LOD) was 10 pM.…”
Section: D Nanostructuresmentioning
confidence: 99%
“…Reproduced with permission. [79] Copyright 2015, The Royal Society of Chemistry. D) The superior protein probe PAZ was used to detect miRNAs with the Au NWs as SERS enhanced nanoplatform.…”
Section: D Nanostructuresmentioning
confidence: 99%
“…By using NP‐CNMs, a system that functioned not only as an electrical biosensor but also a SERS‐based optical sensor was developed. Zheng et al conducted mRNA detection by using AgNP‐CNTs via a SERS‐based biosensor . In this study, single‐stranded DNA was introduced onto CNTs to conjugate Ag NPs on the CNT and prepare a SERS‐active substrate.…”
Section: Nanoparticle‐functionalized Cnts and Grp‐based Electrical Anmentioning
confidence: 99%
“…For label-free detection, a variety of SERS-active substrates were designed to improve the Raman enhancement factor, such as hollow Au nanoflowers substrates [ 74 ], silver nanorod array substrates [ 75 ] and SWNTs@AgNPs [ 76 ]. Zheng et al [ 76 ] developed an approach of DNA-templated in situ growth of AgNPs on SWNTs for the sensitive detection of a potential cancer marker miRNA-21. The silica microbeads-conjugated double stranded DNA competitively bound to the target miRNA, forming liberated ssDNA that showed high affinity to SWNTs.…”
Section: Application On the Detection Of Human And Animal Originalmentioning
confidence: 99%